Effect of molecular weight of polymeric additives on formation, permeation properties and hypochlorite treatment of asymmetric polyacrylonitrile membranes - Jung, B; Yoon, JK; Kim, B; Rhee, HW (ELSEVIER SCIENCE BV, 2004)
Asymmetric polyacrylonitrile membranes were prepared via phase inversion process from casting solution composed of synthesized polyacrylonitrile (PAN), dimethylsulfoxide (DMSO), and poly(vinylpyrrolidone) (PVP) of different molecular weights. The effect of molecular weight of PVP in the casting solution on the morphology, water flux was investigated. The effect of hypochlorite treatment on PVP which was entrapped in pore was investigated. As the higher molecular weight of PVP is added, the thicker top layer of the asymmetric membrane is. The top layer of the membrane and the suppression of macrovoid formation strongly depend on the molecular weight of PVP. The addition with different molecular weight of PVPs also changes pure water permeability. It is also found that the substantial amount of PVP is entrapped in the pores, the water flux decreases. The effect of pore-filling depends on the molecular weight of the additive. Using sodium hypochlorite solution, the entrapped PVP was able to be partially removed. The effectiveness of the selective bleach is pronounced for a higher molecular weight of PVR which results in higher water permeability, compared to untreated membranes. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: PHASE-INVERSION MEMBRANES; FIBER ULTRAFILTRATION MEMBRANES; SEPARATION; MICROSTRUCTURES; BLEND; PVP